Effectiveness of using nanoscale zero-valent iron and hydrogen peroxide in degrading sulfamethazine in water - Lin, Chia-Chang; Cheng, Ya-Jung (Journal of the Taiwan Institute of Chemical Engineers, 2021)
•An effective degradation of sulfamethazine using the nZVI/H2O2 process with the mass-produced nZVI was achieved.•Complete degradation of sulfamethazine was obtained in 20 min using the nZVI/H2O2 process with the mass-produced nZVI.•This investigation provides a novel treatment of sulfamethazine-contaminated water. This investigation elucidates the performance of using nanoscale zero-valent iron (nZVI) and hydrogen peroxide (H2O2) in the degradation of sulfamethazine in water. nZVI was mass-produced using the reductive precipitation method in a rotating packed bed with blade packings. The dependences of the degradation efficiency of sulfamethazine on pH, H2O2 concentration, nZVI dosage, and initial sulfamethazine concentration were assessed. The degradation efficiency of sulfamethazine at pH 3 substantially exceeded those at other pH 5, 7, 9, and 11. An optimal H2O2 concentration for degrading sulfamethazine (10 mg/L) at pH 3 and an nZVI dosage of 28 mg/L was 1 mmol/L. The degradation efficiency of sulfamethazine increased as the nZVI dosage was increased and the initial sulfamethazine concentration was decreased. The degradation efficiency of sulfamethazine (10 mg/L) within 5 min was 99% at pH 3 with an H2O2 concentration of 1 mmol/L and an nZVI dosage of 28 mg/L. However, the degradation efficiency of sulfamethazine (10 mg/L) using the nZVI/H2O2 process with commercial nZVI from Sigma-Aldrich was 4% at 5 min under the same conditions. Accordingly, the nZVI/H2O2 process with the mass-produced nZVI has considerable potential for the enhanced degradation of sulfamethazine in water. [Display omitted]